Intuitionistic fuzzy G-Congruences on a Lattice - Nair, Latha S (IJRDO -JOURNAL OF MATHEMATICS, 2016)
he definition of reflexivity of a intuitionistic fuzzy relation R on a set S isgeneralized. Intuitionistic fuzzy equivalence relations on a given set and intuitionistic fuzzycongruence relation on a lattice are studied under this generalized setting. We prove thatthe set of all intuitionistic fuzzy G-congruence relations on a lattice L forms a lattice, andalso we study modularity of a special class of this lattice.